FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEPUTUSAN PETANI DALAM ADOPSI INOVASI KALENDER TANAM TERPADU DI KECAMATAN GEDANGSARI KABUPATEN GUNUNG KIDUL - Muhammad Iqbal Akbar; Suminah Suminah; Agung Wibowo (AGRITEXTS: Journal of Agricultural Extension, 2018)
Climate change is a natural phenomenon that has occurred at all levels of the continent or country, as well as specific location at sub-district level in relatively small area. Various weather and climate information services such as data afforded by government institutes, research institutes, and universities are far from the reach of farmers.  This  research  aims  to:  study  the  influence  of  socio-economic  factors, attitudes, access to communication media, needs and characteristics / nature of simultaneous or partial innovation toward farmers’ decision in Integrated Katam innovation.   The location of the study was deliberately determined in Tegalrejo and Watugajah because the village received the Integrated Katam program in Gedang Sari Sub-district,   Gunung   Kidul.   The   sampling   method   was   done   randomly   using proportional random sampling with 50 people. Multiple linear regression is used as the data analysis. The results showed that: (1) characteristics of respondent farmers in socioeconomic factors were classified as moderate, attitudes wre classified as neutral, access of communication media were infrequently utilized, social needs level and characteristic  /  nature  of  innovation  were  quite  appropriate;  (2)  socio-economic factors, attitudes, needs, access to communication media and characteristics / nature of innovation simultaneously have significant effects on the adopted decision of Integrated Katam innovation; (3) socioe-conomic factors, attitudes, needs and characteristics / nature of innovation have significant effects on decision to adopt innovation Integrated Katam partially while communication media access was not significant; (4) Decision making adoption of Integrated Katam innovation in Gedang Sari was moderate